Recognition of Mental Illness As A Consequence of Medical Workers In The Procedure For Claiming Work Accident Insurance In Indonesia - Irma Nafa Nabila; Salsabila Maulida Rahmah; Fajar Rachmad Dwi Miarsa; Rizal Haliman; Danggur Feliks (PT. Banjarese Pacific Indonesia, 2024)
Medical personnel are a group of workers who are at high risk of experiencing work accidents and occupational diseases. One type of occupational disease that is often experienced by medical personnel is mental illness. Mental illnesses experienced by medical workers can have a negative impact on their quality of life, performance and productivity. Therefore, medical personnel who suffer from mental illness have the right to receive protection and guarantees from the government and employers. However, in practice, medical personnel who suffer from mental illness often experience difficulties in submitting claims. The research entitled